The Effectiveness of Group Counseling Cognitive Restructuring Techniques to Increase the Self-confidence of Students - Humaira Dwi Setiyowati; Nyoman Dantes; Kadek Ari Dwiarwati (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Students' lack of confidence in completing various assignments given by the teacher shows that students need more self-confidence. This study aims to determine the effectiveness of group counseling with cognitive restructuring techniques on students' self-confidence. This quantitative research study uses a quasi-experimental approach using a Nonequivalent Control Group design. The population is 314 from two different classes. Ten students were selected as samples from the two classes, and the selected subjects were identified as having low self-confidence. The pre-test and post-test were used to determine the difference in scores shown by the control and experimental classes. Data was collected through interviews and questionnaires and distributed to students involved as research subjects. Then, the data were analyzed with quantitative descriptive and inferential descriptive. The results show the difference in scores between the control and experimental groups. In the experimental class, a post-test score of 133.5 was obtained by the experimental class, and the control class obtained a post-test score of 112. The difference in the mean post-test scores indicated that the class that received the cognitive restructuring group counseling treatment showed a change in behavior as evidenced by the post-test scores, which were higher than the class that did not receive the cognitive restructuring group counseling treatment. It indicates the acceptance of Ha so that there is effectiveness contributed by group counseling with cognitive restructuring techniques in increasing student self-confidence.